2007
DOI: 10.1017/s1751731107666105
|View full text |Cite
|
Sign up to set email alerts
|

Net nutrient absorption and liver metabolism in lactating dairy cows fed supplemental dietary biotin

Abstract: The effect of feeding supplemental biotin on net absorption and metabolism of nutrients by the portal-drained viscera (PDV; the gut, pancreas, spleen and associated fat) and liver of lactating dairy cows was measured. Three cows in early to mid-lactation catheterised for measurements of net nutrient absorption and metabolism by the PDV and liver were fed a total-mixed ration with or without supplemental biotin at 20 mg/day using a switch-back design (ABA v. BAB) with three 2-week periods. There were no effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Similar to most studies [26,27], the present study observed no effect on plasma glucose with biotin supplementation, but some studies have observed an increase [23]. Research has indicated that a large proportion of propionate is metabolized in the rumen wall, where it enters the gluconeogenic pathway, drastically reducing glucose utilization by gastrointestinal tissues and leaving more glucose available for other tissues [22].…”
Section: Discussionsupporting
confidence: 85%
“…Similar to most studies [26,27], the present study observed no effect on plasma glucose with biotin supplementation, but some studies have observed an increase [23]. Research has indicated that a large proportion of propionate is metabolized in the rumen wall, where it enters the gluconeogenic pathway, drastically reducing glucose utilization by gastrointestinal tissues and leaving more glucose available for other tissues [22].…”
Section: Discussionsupporting
confidence: 85%
“…However, blood glucose and insulin concentrations were unchanged with BI addition, and were consistent with the limited milk lactose yield response. Furthermore, other studies found that supplementing 20 mg/day of BI in dairy cow diets had no effect on pyruvate carboxylase and propionyl‐CoA carboxylase gene expressions and glucose net release in the liver (Ferreira & Weiss, 2007; Reynolds et al, 2007). Zimmerly and Weiss (2001) and Reynolds et al (2007) also reported unaltered blood glucose and insulin concentrations with BI addition in dairy cows.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other studies found that supplementing 20 mg/day of BI in dairy cow diets had no effect on pyruvate carboxylase and propionyl‐CoA carboxylase gene expressions and glucose net release in the liver (Ferreira & Weiss, 2007; Reynolds et al, 2007). Zimmerly and Weiss (2001) and Reynolds et al (2007) also reported unaltered blood glucose and insulin concentrations with BI addition in dairy cows. These results above showed that supplementing BI probably could not increase glucose supply of dairy cows.…”
Section: Discussionmentioning
confidence: 99%